Analisis Timbulan Sampah Vegetasi Semak Belukar dari Pemeliharaan Rutin dengan Metode Sampling - Helga Maritza Putri; Syadzadhiya Qothrunada Zakiyayasin Nisa' (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Oil and gas industry activities have the potential to produce high carbon emissions, so Green Open Space (RTH) is needed as an effort to mitigate environmental impacts. Shrub vegetation that grows in RTH areas requires routine maintenance, but this process produces vegetation waste that has not been studied quantitatively. This study aims to analyze the generation of shrub vegetation waste using a sampling method as a basis for sustainable waste management planning. The method used is sampling on a 1 m³ cube-shaped plot in three locations with different vegetation characteristics. Cutting is done manually using simple tools, then the waste produced is put into a measuring box to calculate its volume. The results show that sample point 1 produces 1.00 m³, sample point 2 is 0.50 m³, and sample point 3 is 0.30 m³. The average volume of shrub waste generation is 0.60 m³ per square meter. This data is important for planning the capacity of equipment, labor, and temporary waste disposal locations. In addition, the characteristics of waste that is easy to dry and has a high organic content opens up the potential for reuse as compost or biomass. This method has proven to be effective and efficient in supporting environmentally friendly vegetation waste management strategies as well as part of compliance with environmental regulations such as PROPER.